A Differential Threshold of Breakfast, Caffeine and Food Groups May Be Impacting Mental Well-Being in Young Adults: The Mediation Effect of Exercise - Begdache, Lina; Kianmehr, Hamed; Najjar, Helen; Witt, Dylan; Sabounchi, Nasim S. (Frontiers in Nutrition, 2021)
Diet and exercise are known to influence mental health. However, the interaction between diet, dietary practices, and exercise and its impact on the mood of young adults (YA) is poorly understood. YA are inherently at risk for mental distress. They tend to consume a low-quality diet and are generally active. The purpose of the study was to assess these relationships through validating causal loop diagrams (CLD) that describe these connections by using a system dynamic (SD) modeling methodology. Adults 18-29 years were invited to complete the Food-Mood questionnaire. The anonymous questionnaire link was distributed to several institutional listservs and via several social media platforms targeting young adults. A multi-level analysis, including machine learning techniques, was used to assess these relationships. The key findings were then built into gender based CLD, which suggest that a differential repertoire may be needed to optimize diet quality, exercise, and mental wellbeing. Additionally, a potential net threshold for dietary factors and exercise may be needed to achieve mental wellbeing in young adults. Moreover, our findings indicate that exercise produces a positive effect of food groups on mental wellbeing and lessens the negative impact of others known to negatively influence mood.